1979
DOI: 10.1093/ajcp/72.5.848
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tocopherol on High-density Lipoprotein Cholesterol: A Clinical Observation

Abstract: A significant redistribution of cholesterol in lipoproteins following ingestion of large doses of D,L-alpha tocopherol (vitamin E) is documented. In persons with decreased high-density lipoprotein (HDL) cholesterol a complex response occurs, which includes cholesterol redistribution in favor of the HDL fraction, with decreases in very-low-density lipoprotein (VLDL) levels and total triglycerides. The response was studied in five persons with average cholestrol distributions and five persons with cholesterol di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 0 publications
2
16
1
1
Order By: Relevance
“…Hermann et al (30) supplemented human subjects with 600 IU of = -tocopherol for 30 days; an increase in HDLcholesterol and no change in triglycerides or total cholesterol occurred. These results were not confirmed by other investigators who used the same experimental protocol (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…Hermann et al (30) supplemented human subjects with 600 IU of = -tocopherol for 30 days; an increase in HDLcholesterol and no change in triglycerides or total cholesterol occurred. These results were not confirmed by other investigators who used the same experimental protocol (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…Whether HDL cholesterol concentrations change in humans taking vitamin E supplements remains a controversial topic. Since the late 1970s, vitamin E supplements have been found to increase ( 86,87 ), decrease ( 88 ), or leave unchanged ( 89 ) the circulating HDLcholesterol concentrations. The differences in these outcomes may have to do with the various HDL regulators, as discussed below.…”
Section: Lipoprotein Transportmentioning
confidence: 99%
“…However, several workers showed that vitamin E may slow the progress of atherosclerosis by modifying the synthesis and degradation of lipids in the arterial wall 26 and/or by increasing the proportion of blood cholesterol in the electrophoretic HDL-C fraction. 21 The view that vitamin C supplementation into rats for five weeks or more could affect the concentration of plasma concentrations is further supported by the work of Riemersma and co-workers 16 who showed that low plasma concentrations of vitamin C were related to an increased risk of angina pectoris in men. In addition, they reported that vitamin C levels are lower in cigarette smokers than in nonsmokers.…”
Section: Discussionmentioning
confidence: 97%
“…This result is also in agreement with results reported elsewhere. [21][22][23][24] In 1982, Haeger 25 suggested that when vitamin E is maintained in excess of that provided by a normal diet in humans, it is beneficial in intermittent claudication and perhaps other manifestations of atherosclerosis. However, several workers showed that vitamin E may slow the progress of atherosclerosis by modifying the synthesis and degradation of lipids in the arterial wall 26 and/or by increasing the proportion of blood cholesterol in the electrophoretic HDL-C fraction.…”
Section: Discussionmentioning
confidence: 99%